Painful violaceous pigmentation, a clinical challenge and diagnostic approach in a tropical country - Rojas-Gómez, Oscar Fabián (2022)
Millipedes are not considered poisonous animals, although in some cases their chemical defense mechanisms may be deleterious for human beings, manifesting as erythematous, purpuric and/ or cyanotic lesions alongside local pain and paresthesia. According to the exposure, the clinical condition may progress to moderate and severe lesions such as ulcers and blisters. We describe a case of a male child from the Andean region in Colombia, an area with daily temperatures between 15° and 30° C and 72% average humidity. The boy accidentally stepped on a millipede, and this occurrence became a challenge for its diagnosis amongst staff who provided emergency health care.